(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The significance of acquiring English cannot be under estimated. Though in the present age of multi-nationals more emphasis is laid on acquiring communicative ability and it is perceived as an instrument of upward social mobility and job opportunity but even the scope of verbal expression is confined to a narrow area while the fires impression that we cost on others is made though the written communication. Moreover, if there is any confusion in verbal communication the speaker can explain things using different terms or repeating the matter or through gestures etc. but if there is any confusion in written communication, due to in competency, the matters remain unexplained forever. Therefore the students must acquire competency in mechanics of writing-spelling is one these use of wrong spellings make the text unintelligible and its wears the beauty of the context- even if the matter is appropriate and presentation effective, wise spelt words can nullify its appropriate and presentation effective, wise spelt words can nullify its appropriate and presentation effective, wise spelt words can nullify its impact on readers, it hampers the personality of writer by deteriorating his image as a scholar English is a language which has many phones and even small change in spelling can alter the meaning of entire text To avoid This problem care should be taken us to correct spelling . Hence an attempt is made w here to study spelling in English among students of IX class